Statistical Analysis in Service Quality: A Review - Dr. Mohd. Imran Siddiquei, Mr. Shashank kathpal, Mrs. Rekha Bawa (International Journal of Advanced Science and Technology, 2020)
This research focuses on literature review of service quality, in terms of the statistical test used by various scholars while evaluating service quality in different sectors using service quality models. Servqual model is considered as one of the most widely used models while evaluating service quality. In service quality there are various gaps that are identified by servqual, allthese gaps require measurement. Various scholars have used different types of statistical tests for their empirical studies in different sectors like banking,education,hospitality, transport etc. In this study all the major indexes like Scopus, Wos, ProQuest, Ebsco have been searched for studies related to statistical tests used in different studies of service quality. This paper will provide a widespread review of researches with a major focus on variousstatistical tests used to measure gaps as mentioned in service quality models.